Effect of Rice Husk Ash on High-Temperature Mechanical Properties and Microstructure of Concrete - Weihong Wang; Yunfang Meng; Dezhi Wang (Kemija u Industriji, 2017)
Effects of rice husk ash (RHA) on the strength and temperature resistance of concrete were investigated. Different amounts of cement in concrete were replaced by RHA and fly ash (FA), used as mineral admixtures, under the condition of a constant binder content. The compressive strength and temperature resistance were tested at different temperatures. The results show that mixing concrete with the appropriate amounts of RHA can improve its compressive strength. At 800 °C, the strength is 50 % greater than that of normal concrete (NC). Thus, RHA can improve the strength and temperature resistance of concrete.